Vertical distributions of heavy metals in bottom sediment in Xi-xi national wetland - CHEN Ru-hai; ZHAN Liang-tong; CHEN Yun-min; HU Hong-zhi (浙江大学学报. 农业与生命科学版)
A special sampler was made to drill out long and integrated sediment samples from Xi-xi national wetland of Zhejiang Province, and the contents of Cu, Pb and Zn in the sediments at different depths were tested to evaluate pollution degree of the heavy metals, as well as to determine their distribution along depth in the wetland using the method of geoaccumulation index. The tests and evaluation results showed that the sediments were moderately polluted within 0.6 m below the river bed, and not polluted at the depth deeper than 0.6 m. The concentration of heavy metals in the shallow sediments was found to be higher than that in pore water, which was in turn much more than that in the above water. Heavy metals in pore water of sediments could be released into the above water due to the concentration gradient, indicating that the water quality in the wetland could not be completely recovered only by replacing the polluted water with clean water, but needed to dredge the contaminated sediments in the wetland. The top 0.6 m sediment should be dredged from an economic point of view.